EVALUASI PENGEMBANGAN EKOWISATA DI KAWASAN TAHURA NGURAH RAI - PUTU IKA WAHYUNI; IPG ARDHANA; I NYOMAN SUNARTA (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Since January 1992 MIC has initiate Tahura Ngurah Rai are as a ecotourism area, offering programs such as :Mangrove Education Tour & Tracking, Bird Watching; Finishing; Mangrove Tree Plantation or Adoption, Canoeing, andBoating programs. However, its growth has not me the management’s targets in term of the number of visitors, improvedfacilities available, and the surrounding Tahura are – especially its cleanliness-these are far from expectation standard.The evaluation of eco-tourism area of Tahura is aimed at understanding the profile of the eco-tourism area and tounderstand to what extent the ecotourism has met criteria/principles issued in the national workshop. This ecotourism willoffer recommendations designed in relation to programs that has not been working so far after identifying obstacles oftheir implementation.The method used in the evaluation of this eco-tourism area I descriptive analysis by analyzing interview data,observations, and literature studies. These descriptive data then are measured against criteria and principles of nationaleco-tourism.Since March 12, 2007 Mangrove forest area is under the management of BPHM-wil-I continuing JICA ICprogram. Facilities available in the area are as follows; Wood Trails, 5 Huts along the trail, Floating Decks, 2 ViewingTowers; MIC/BPHM Office Building, Touch Pools, Seeding area, and a Monitor Pool. These facilities right now are stillin good condition and can be used to implement the eco-tourism programs.From the 6 programs offered, the Mangrove Education Tour & Tracking Program gets the most interests fromvisitors than the other 5 programs. From 9 criteria used to evaluate the programs, the outcome is as follows: 1) Beingsensitive to and respecting socio-cultural values and religious tradition of local community (88% met); 2) Showingconcern, commitment, and responsibility to natural conservation and cultural heritage (95,24% met); 3) Provideinterpretation that facilities visitors to enjoy nature and increase their awareness and concern for nature (85,71% met); 4)Educational in which there is a mutual learning between visitors and community (100% met); 5) Its development be basedon local community through agreement (20% met); 6) Empower and optimize participant and at the same time bring forthon going contribution to the local community (0% met), 7) To go by existing rules and law (100% met); 8) Consistentlysatisfy the visitors (50% met), 9) Being marketed and promoted openly and accurately to meet expectation – that is amarketing responsibility (100% met). Generally the result from comparison between ecotourism program withprincipal/criteria are as follows : from nine principles that already explained only the fifth and sixth principal whose itsdevelopment less than 50%, based on those condition above it can be conclude that mangrove ecotourism developmentalready fulfill the principal/criteria of national ecotourism. Important points of recommendations to the management areas follows; community participation; retributions, waste management; improvement of programs that are not working;and eco-tourism management under a solid institution.